2012
DOI: 10.1038/nprot.2012.083
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a humanized mouse model with both human immune system and liver cells to model hepatitis C virus infection and liver immunopathogenesis

Abstract: Establishing a small animal model that accurately recapitulates hepatotropic pathogens, including hepatitis C virus (HCV) infection and immunopathogenesis, is essential for the study of hepatitis virus–induced liver disease and for therapeutics development. This protocol describes our recently developed humanized mouse model for studying HCV and other hepatotropic infections, human immune response and hepatitis and liver fibrosis. The first 5-h stage is the isolation of human liver progenitor and hematopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 20 publications
0
58
0
Order By: Relevance
“…Finally, humanized mice with human immune system and hepatocytes is the only model, which upon infection triggers responses similar to humans, i.e., hepatitis and fibrosis. [44][45][46][47] Genetically modified mice Genetically modified animals are becoming a more frequent tool to study liver pathophysiology as well as the roles of metalloproteinases. The liver consists of several cell types and it is not easy to target them specifically.…”
Section: Unspecific Overall Liver Damagementioning
confidence: 99%
“…Finally, humanized mice with human immune system and hepatocytes is the only model, which upon infection triggers responses similar to humans, i.e., hepatitis and fibrosis. [44][45][46][47] Genetically modified mice Genetically modified animals are becoming a more frequent tool to study liver pathophysiology as well as the roles of metalloproteinases. The liver consists of several cell types and it is not easy to target them specifically.…”
Section: Unspecific Overall Liver Damagementioning
confidence: 99%
“…Although attempts at humanization of available pig has not yet been published, mature teratomas developed after injection of human pluripotent stem cell injection into RAG mutant SCID pigs 35 . The success of the SCID mouse for xenotransplantation, cancer therapy, human specific disease modeling, and stem cell therapies is well documented 43,44,46 and can be expected to extend to swine models. Swine immune parameters more similar to the human, as described above, and in addition, the swine immune gene component or "immunome" is very similar to humans 47 …”
Section: Large Animal Models: the Opportunities Of The Scid Pigmentioning
confidence: 99%
“…Coveted for the lack of xenograft rejection and human tissue differentiation, humanized mice can provide the environment to harbor and allow differentiation of human HSC 43 , allowing a model of human immune response to host species-restricted pathogens such as HIV or hepatitis C virus 44 . Early research on various strains of humanization of SCID mouse variants identified that potential mouse cell to human cell interactions were interfering with engraftment success.…”
Section: Large Animal Models: the Opportunities Of The Scid Pigmentioning
confidence: 99%
“…Similarly, hepatitis B virus X transgenic mice develop liver tumors after 13-24 months [19]. A humanized mouse model to model HCV infection has also been established [20]. Abusive alcohol consumption is another leading cause of liver damage and a contributive factor for cirrhosis and liver cancer [21].…”
Section: Cancer Cell-centric Modelsmentioning
confidence: 99%